If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(-5x + -1) = 2 Reorder the terms: 7x + -1(-1 + -5x) = 2 7x + (-1 * -1 + -5x * -1) = 2 7x + (1 + 5x) = 2 Reorder the terms: 1 + 7x + 5x = 2 Combine like terms: 7x + 5x = 12x 1 + 12x = 2 Solving 1 + 12x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 12x = 2 + -1 Combine like terms: 1 + -1 = 0 0 + 12x = 2 + -1 12x = 2 + -1 Combine like terms: 2 + -1 = 1 12x = 1 Divide each side by '12'. x = 0.08333333333 Simplifying x = 0.08333333333
| 10-x=2 | | 5*a*b*8*b^2= | | (8x-8y)(8x-8y)= | | 3v^2+v-2=0 | | 15x-5=-5+3 | | 6(x-1)+12=5(x+2)+11 | | 22=j-45 | | 2x^2+6X=x^2+27 | | 4x-8-7x+2=12 | | 3x+7=26 | | -18=-9t+t^2 | | 2(x-1)=3(x+3) | | 3=3y | | 4v^2+20v+25=0 | | 4(7y-5)-(9y+4)= | | 8(3y-8)-(4y+2)= | | 8m+7=2m+3 | | 5w^2+16w+3=0 | | -12(9+3m)=8-7m | | b-8=5b-2 | | -13n-45=-10(n+6) | | 3=x+9-15 | | 4b-2b=2+b+6+6 | | 6a-3=4a-1 | | 10-10k=18-12k | | 2y+3=y-5 | | 13=9+x | | -21+2p=5p+6 | | 2x^3-5x^2-x+16=0 | | 0.027m+2=0.035m | | 2x^3-5x^2-x+16=9 | | 1+n-7-10=6n+14 |